2012
DOI: 10.1016/s1734-1140(12)70763-6
|View full text |Cite
|
Sign up to set email alerts
|

Acute and repeated treatment with the 5-HT7 receptor antagonist SB 269970 induces functional desensitization of 5-HT7 receptors in rat hippocampus

Abstract: Abstract:Background: SB 269970, a 5-HT 7 receptor antagonist may produce a faster antidepressant-like effect in animal models, than do antidepressant drugs, e.g., imipramine. The present work was aimed at examining the effect of single and repeated (14 days) administration of SB 269970 on the 5-HT 7 receptor in the hippocampus. Methods: The reactivity of 5-HT 7 receptors was determined using 5-carboxamidotryptamine (5-CT), which increased the bursting frequency of spontaneous epileptiform activity in hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Desensitization of 5-HT 7 receptors was also observed after antagonist treatment (Tokarski et al, 2012b). Thus, systemic treatments of animals should be carefully designed to minimize 5-HT 7 receptor desensitization; in this respect, a preferential use of agonists with a short half-life, such as LP-211 and related compounds (Hedlund et al, 2010) might be considered preferentially.…”
Section: Involvement Of 5-ht7 Receptors In Pathologymentioning
confidence: 98%
“…Desensitization of 5-HT 7 receptors was also observed after antagonist treatment (Tokarski et al, 2012b). Thus, systemic treatments of animals should be carefully designed to minimize 5-HT 7 receptor desensitization; in this respect, a preferential use of agonists with a short half-life, such as LP-211 and related compounds (Hedlund et al, 2010) might be considered preferentially.…”
Section: Involvement Of 5-ht7 Receptors In Pathologymentioning
confidence: 98%
“…Different strategies have allowed to investigate the properties of this receptor population related to modulation of anxiety levels. Studies on this issue have been carried out on transgenic mice lacking the 5-HT7-R (Guscott et al, 2005;Hedlund and Sutcliffe, 2007) or by administration of selective 5-HT7-R antagonists (e.g., SB-269970, SB-258719, and SB-656104) (Forbes et al, 2002;Hagan et al, 2000;Thomas et al, 1998;Tokarski et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The data demonstrated that both single and repeated SB 269970 administration lowered the level of mRNA of those G proteins (Gas and Ga12) which couple to the 5-HT 7 receptor in the hippocampus [103]. Repeated treatment with SB 269970 also decreased the density of 5-HT 7 receptors [98]. These effects differed markedly from the effects of the antidepressant imipramine, which altered neither the level of the mRNAs nor the density of 5-HT 7 receptors when administered once or repeatedly for 14 days.…”
Section: +mentioning
confidence: 92%
“…-free incubation conditions [98]. The mechanisms underlying the observed attenuation of the excitatory effect of the 5-HT 7 receptor activation by SB 269970 may potentially be related to either the decreased receptor density or the modification in the capacity of the receptor to activate G protein, changes in G protein expression or phosphorylation, or modifications at the level of effectors.…”
Section: +mentioning
confidence: 99%